1996
DOI: 10.1073/pnas.93.6.2280
|View full text |Cite
|
Sign up to set email alerts
|

A defect in glycosylphosphatidylinositol (GPI) transamidase activity in mutant K cells is responsible for their inability to display GPI surface proteins.

Abstract: The final step in the pathway that provides for glycosylphosphatidylinositol (GPI) anchoring of cellsurface proteins occurs in the lumen of the endoplasmic reticulum and consists of a transamidation reaction in which fully assembled GPI anchor donors are substituted for specific COOH-terminal signal peptide sequences contained in nascent polypeptides. In previous studies we described a human K562 cell mutant line, designated class K, which assembles all the known intermediates of the GPI pathway but fails to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 22 publications
2
32
0
Order By: Relevance
“…In yeast (Schizosaccharomyces pombe) and human cells, gpi8 mutants are defective in GPI attachment and cause a decrease in cell surface display of GPI-anchored proteins (Benghezal et al, 1996;Chen et al, 1996;Yu et al, 1997). The Arabidopsis genome contains a single gene (GPI8) that encodes a protein with high sequence similarity to yeast (43.8% identity) and human (45.7% identity) GPI8 and contains the postulated protease catalytic site that is conserved in C13 clade of cysteine proteases (Supplemental Figures 6A and 6B) (Zacks and Garg, 2006).…”
Section: Lre-cyfp Localization In the Filiform Apparatus Is Disruptedmentioning
confidence: 99%
“…In yeast (Schizosaccharomyces pombe) and human cells, gpi8 mutants are defective in GPI attachment and cause a decrease in cell surface display of GPI-anchored proteins (Benghezal et al, 1996;Chen et al, 1996;Yu et al, 1997). The Arabidopsis genome contains a single gene (GPI8) that encodes a protein with high sequence similarity to yeast (43.8% identity) and human (45.7% identity) GPI8 and contains the postulated protease catalytic site that is conserved in C13 clade of cysteine proteases (Supplemental Figures 6A and 6B) (Zacks and Garg, 2006).…”
Section: Lre-cyfp Localization In the Filiform Apparatus Is Disruptedmentioning
confidence: 99%
“…3A). Gaa1p and Gpi8p were the first to be identified through genetic approaches (143)(144)(145)(146) and were subsequently shown to form a complex (147); the other subunits were identified mainly because they specifically coimmunoprecipitated with the GPI8/Gpi8p-GAA1/Gaa1p complex (148)(149)(150)(151). GPITs from Drosophila melanogaster, Caenorhabditis elegans, and Arabidopsis thaliana are similar to the mammalian/ yeast enzyme.…”
Section: Transfer Of Gpis To Proteinmentioning
confidence: 99%
“…A human mutant cell line termed class K that is defective in attachment of GPI (Mohney et al, 1994;Chen et al, 1996) is due to a defect in the human GPI8 gene (Yu et al, 1997). Microsomal membranes of class K cells did not have GPI transamidase activity (Chen et al, 1996;Yu et al, 1997). It was therefore suggested that Gpi8p is a component of the GPI transamidase (Benghezal et al, 1996;Yu et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…GPI8 encodes a protein with homology to members of a family of cysteine proteases (Benghezal et al, 1996), one of which, a jack bean asparaginyl endopeptidase, showed transamidase activity in vitro (Abe et al, 1993). A human mutant cell line termed class K that is defective in attachment of GPI (Mohney et al, 1994;Chen et al, 1996) is due to a defect in the human GPI8 gene (Yu et al, 1997). Microsomal membranes of class K cells did not have GPI transamidase activity (Chen et al, 1996;Yu et al, 1997).…”
Section: Introductionmentioning
confidence: 99%